Application of Therapy Pursed Lips Breathing Regarding the Increase in Oxygen Saturation of Pulmonary Tuberculosis Patients in the Lung Inpatient Room at Raden Mattaher Hospital, Jambi Province - Lala; Sulistiawan, Andika (Jurnal Pinang Masak, 2024)
Tuberculosis is an infectious disease caused by infection with the bacteria Mycobacterium tuberculosis which can attack various organs of the body, especially the lungs in the lung parenchymal tissue. One of the symptoms that can appear in pulmonary TB patients is shortness of breath, where the shortness felt will cause oxygen saturation to decrease below normal limits. Interventions that can be given to patients who experience shortness of breath can be done by administering bronchodilator drugs, additional oxygen, positioning and non-pharmacological breathing exercises. One non-pharmacological therapy that can be used to increase patient saturation is the pursed lips breathing exercise. The design of this scientific paper uses a case report design. The research subjects used were patients with pulmonary tuberculosis. Data was carried out used descriptive analysis by looking at oxygen saturation before and after giving pursed lips breathing therapy for 5 days of application. Application showed that after applying pursed lips breathing for 5 days, there is an increase in oxygen saturation in pulmonary tuberculosis patients, namely from 90% to 97%. The application of pursed lips breathing can increase oxygen saturation in pulmonary tuberculosis patients, so this therapy can be used as an intervention to increase oxygen saturation.